Fundamental Relation on HvBE-Algebras - Iranmanesh, Farzad; Ghadiri, Mansour; Borumand Saeid, Arsham (Bulletin of the Section of Logic, 2023)
In this paper, we are going to introduce a fundamental relation on \(H_{v}BE\)-algebra and investigate some of properties, also construct new \((H_{v})BE\)-algebras via this relation. We show that quotient of any \(H_{v}BE\)-algebra via a regular regulation is an \(H_{v}BE\)-algebra and this quotient, via any strongly relation is a \(BE\)-algebra. Furthermore, we investigate that under what conditions some relations on \(H_{v}BE\)-algebra are transitive relations.